Postsecondary ADHD Documentation Requirements: Common Practices in the Context of Clinical Issues, Legal Standards, and Empirical Findings. (August 2015) - Lindstrom, Will; Nelson, Jason M.; Foels, Patricia
Objective: To evaluate the information postsecondary institutions require when determining disability service eligibility for students with reported ADHD.Method: ADHD documentation requirements of 200 U.S. institutions were surveyed by reviewing guidelines posted on disability services websites.Results: Whereas virtually all institutions required documentation, findings revealed significant variability in requirements across institutions. Required variables most often included a qualified evaluator (80%), diagnostic statement (75%), and identification of substantial limitations (73%), but only 5 of 46 evaluated variables were required by at least 50% of institutions. Supportive data such as diagnostic criteria, standardized assessment results, and rationale for accommodations were rarely required.Conclusion: The majority of institutions required little to verify ADHD as a disability. Furthermore, there was little agreement on what components are essential for verification. When integrated with research, a large portion of guidelines failed to address identified weaknesses in ADHD diagnosis and disability determination.